Controle de lesões corticosas na casca e qualidade de frutos de abacaxi cv. turiaçu fertilizado com Boro - Santos, Auderes Watyson de Oliveira (2013)
Maranhão of the pineapple variety Turiaçu that is traditionally grown in the city of Turiaçu -MA assumes great regional importance , since they have wide acceptance in the market . Despite their importance in many aspects of growing this variety yet to be studied more deeply. One problem that detracts from the commercial value of cv . Turiaçu currently is the presence of lesions on the skin of the fruit . The objective of the study was to evaluate different doses of boron in control lesions in the bark and fruit quality of pineapple cv. Turiaçu. The experiment was conducted under field conditions in the city of Turiaçu - MA in the village of Serra Paz Spacing was 1.0 x 0.30 m and the experimental design was a randomized block design with 6 treatments and 4 replications and the treatments different doses of boron were : T1 - control , T2 - 2.0 kg ha- 1 , T3 - 4.0 kg ha - 1 , T4 - 6.0 kg ha - 1, T5 - 8.0 kg . ha- 1 and T6 - 10 kg ha - 1 . The doses of boron applied foundation, levels of 6, 8 and 10 kg ha- 1, promote significant reduction in the number of injuries corticosas typical (severe) compared to the control , with significant improvement of the appearance of the fruit . The most effective treatment (10 kg ha- 1), caused a 60% reduction in the number of lesions, confirming the strong association of the disorder with boron deficiency . The biometric characteristics , the physico - chemical pulp and juice as well as the number of pups per plant showed no significant differences in response to different concentrations of boron. The concentration of boron foliar B was significantly influenced by increasing doses of boron in the soil . In the most effective treatment for control of injuries corticosas (10 kg ha- 1), the boron content was at the proper level for the crop. Prospecting disturbance in production areas confirms that the problem of high incidence of lesions in the fruits is a widespread phenomenon in the region, in that the frequency of 3 or more fruits with lesions was greater than 90% in the sampled areas